(untitled) (Journal of Modern Mechanical Engineering and Technology, 2016)
Two vane type angle of attack sensors, small and large, are tested on the suction surface of a wing of an unmanned aerial vehicle to evaluate the wing interference with angle of attack reading. Tests are performed in the University of Manitoba¢‚¬„¢s wind tunnel with the maximum Reynolds number of 4.5 x 105 to find the optimal location to place sensors on the wing. Each angle of attack sensor is tested at four positions on the wing to investigate the impact of flow deflection caused by the presence of the wing on the sensor readings. Results show that readings are highly sensitive to the normal clearance between the wing and the angle of attack sensor. Accuracy of sensor readings increases by increasing normal clearance. Spanwise placements indicate that the minimum wing interference with angle of attack sensor readings occurs when the sensor is placed beyond the wing tip. To investigate the effect of ailerons on angle of attack sensor readings, sensors are also tested with half, full and with no aileron deflection positions. The effect of aileron deflection is noticeable in large angle of attack sensor readings, while it has a negligible effect on the small sensor readings.